Evaluation Of Adherence To The Use Of Anti-Diabetic Medicine In Type 2 Diabetes Mellitus Patient At Primary Health Care Gombong 1 - Chondrosuro Miyarso; Nadea Murpratami; Endang Yuniarti; Muh Husnul Khuluq (Jurnal EduHealth, 2023)
Background, Diabetes is a chronic metabolic nuisance disease that is signed by a high level of blood sugar more than a normal level. For diabetes mellitus type 2 patient, medicine consumption adherence is a very important thing to control the level of blood sugar in order to stay stable and decrease the complication risk. Research purpose, To know patient characteristic correlation including gender, age, education level, occupation, income, suffering duration, the amount of medicine that is used, complication, by adherence level of the use of anti-diabetes medicine. Research method, Quantitative analysis used a cross-sectional design. The sampling technique used total sampling. the sample used is 62 respondents. The adherence level was measured by the MMAS-8 questionnaire. Data analysis used the Chi-Square test and Ordinal Logistic Regression test. Research result, The adherence level of the use of anti-diabetes medicine in the non-adherence category are 30 respondents (48,4), quite adherence are 21 respondents (33,9), and adherence category are 11 respondents (17,7). Base on Chi-Square test result, there is a significant correlation between age group and adherence level (p=0,034) and there is no a significant correlation between gender (p=0,733), education level (p=0,891), occupation (p=0,059), income (p=0,830), suffering duration (p=0,610), complication disease (p=0,759), and the amount of medicine that is used (p=0,373) with the adherence level. The result of multivariate analysis shows age group 45-60 years old is a dominant factor that has an influence on the level of non-adherence use of medicine with a value of p=0.034 (OR=0.292, 95CI=0.091-0.939). Conclusion, Patients are classified as non-adherence to the use of anti-diabetes medicine (48,4). There is a significant correlation between age group and the adherence level. The age group 40-60 years old is a dominant factor that influences the non-adherence to the use of anti-diabetes medicine. Suggestion, Further research is needed to use a bigger sample, research the family support factor with the adherence level of the use of anti-diabetes medicine, and analyze the long-suffering factor with the level of adherence using the more varied choices.